Regulatory Dendritic Cells, T Cell Tolerance, and Dendritic Cell Therapy for Immunologic Disease - Ness, Sara; Lin, Shiming; Gordon, John R. (Frontiers in Immunology, 2021)
Dendritic cells (DC) are antigen-presenting cells that can communicate with T cells both directly and indirectly, regulating our adaptive immune responses against environmental and self-antigens. Under some microenvironmental conditions DC develop into anti-inflammatory cells which can induce immunologic tolerance. A substantial body of literature has confirmed that in such settings regulatory DC (DCreg) induce T cell tolerance by suppression of effector T cells as well as by induction of regulatory T cells (Treg). Many in vitro studies have been undertaken with human DCreg which, as a surrogate marker of antigen-specific tolerogenic potential, only poorly activate allogeneic T cell responses. Fewer studies have addressed the abilities of, or mechanisms by which these human DCreg suppress autologous effector T cell responses and induce infectious tolerance-promoting Treg responses. Moreover, the agents and properties that render DC as tolerogenic are many and varied, as are the cells’ relative regulatory activities and mechanisms of action. Herein we review the most current human and, where gaps exist, murine DCreg literature that addresses the cellular and molecular biology of these cells. We also address the clinical relevance of human DCreg, highlighting the outcomes of pre-clinical mouse and non-human primate studies and early phase clinical trials that have been undertaken, as well as the impact of innate immune receptors and symbiotic microbial signaling on the immunobiology of DCreg.